Impacts of the COVID-19 Pandemic on Tourism in Ouro Preto – MG - Santos Oliveira, Elielton dos; Lana Pinto, Gabriela Maria de; Lescura, Carolina; Carvalho Gonçalves Knupp, Marcos Eduardo (Anais Brasileiros de Estudos Turísticos, 2021)
The year 2020 markedly became a period of major changes in human history. The pandemic caused by the new coronavirus, COVID-19, created an unprecedented economic crisis, ocausing a temporary halt in several activities worldwide and a movement to reflect on new ways of creating more responsible and innovative tourism. In view of this scenario, the present work seeks to analyze the impacts, especially economic ones, arising from the pandemic of the new coronavirus on tourism in the municipality of Ouro Preto (MG). We opted for the appreciation of the lodging facilities segment due to its occupancy rate which reflects the flow of tourists in the locality. In order to achieve the proposed objective, interviews with semi-structured scripts, questionnaires, and the Tax Comparison of Service of Any Nature - TCSAN of the years 2018, 2019, and 2020 were collected from companies that performed the activity of hosting in the locality. Through this, it was possible to observe some reflexes of this impact, such as the lack of management for periods of crisis and the resumption without planning, resulting in an increase in the number of deaths and contaminated people.